2018
DOI: 10.3747/co.25.3983
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Cannabis Use in Patients with Cancer

Abstract: Background A comprehensive assessment of cannabis use by patients with cancer has not previously been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
73
4
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 11 publications
10
73
4
4
Order By: Relevance
“…Current users tended to primarily use cannabis oil extracts to alleviate multiple symptoms simultaneously, suggesting potential for measurable doses of cannabinoids to substitute for other drugs such as analgesics, anti-emetics, hypnotics, and anxiolytics [5]. These results are consistent with those of other similar studies in Canada which reported on cannabis use in the medical setting prior to legalization [10,11].…”
supporting
confidence: 84%
“…Current users tended to primarily use cannabis oil extracts to alleviate multiple symptoms simultaneously, suggesting potential for measurable doses of cannabinoids to substitute for other drugs such as analgesics, anti-emetics, hypnotics, and anxiolytics [5]. These results are consistent with those of other similar studies in Canada which reported on cannabis use in the medical setting prior to legalization [10,11].…”
supporting
confidence: 84%
“…Comparing our two surveys, we found that legalization was associated with a 26% increase in the prevalence of current cannabis use, from 23•1% to 29•1% (p=0•01). One explanation for this increase might be that in the run-up to legalization news and media outlets were lled with articles about dispensaries opening and closing, [18,26,27] products available, [28,29], and new research [30-33], which may have emboldened more patients to try cannabis. Despite both surveys being anonymous, they may also have felt more comfortable disclosing recreational motivation for use.…”
Section: Comparison Between Before and After Legalization Surveysmentioning
confidence: 99%
“…Under the new legislation, only licensed dispensaries were allowed to sell legal recreational cannabis products, and many unlicensed dispensaries were forced to close while their license applications were being processed [15,17]. At the time of this study, 3 months after legalization, there was only one licensed dispensary open in BC [18]. Widespread publicity of the planned date of legalization created a unique opportunity to observe the use of cannabis in the medical setting both before and after recreational legalization.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 75% of individuals with cancer use cannabis for symptom management, most commonly pain, nausea, and sleep disruption; however, to the best of our knowledge, the evidence base supporting this has been limited. It is important to note at the outset that the majority of the cannabis research conducted in oncology patients lacks the rigor that would be required of most other oncology treatments in practice.…”
Section: Cannabis: Indications Use Versus Evidence Basementioning
confidence: 99%